Some Comparison Theorems in Finsler-Hadamard Manifolds - Borisenko, A. A.; Olin, E. A. (Журнал математичної фізики, аналізу, геометрії, 2007)
We give upper and lower bounds for the ratio of the volume of metricball to the area of metric sphere in Finsler-Hadamard manifolds with thepinched S-curvature. We apply these estimates to find the limit at infinity for this ratio. The estimates derived are the generalization of the result well known in Riemannian geometry. We also estimate the volume growth entropy for the balls in these manifolds. Mathematics Subject Classification: 53C60, 53C20.